Optimizing eating disorder treatment outcomes for individuals identified via screening: An idea worth researching. Issue 11 (10th September 2019) - Taylor, Craig Barr; Graham, Andrea K.; Fitzsimmons‐Craft, Ellen E.; Sadeh‐Sharvit, Shiri; Balantekin, Katherine N.; Flatt, Rachael E.; Goel, Neha J.; Monterubio, Grace E.; Topooco, Naira; Karam, Anna M.; Firebaugh, Marie‐Laure; Ruzek, Josef I.; et al.
Abstract: In recent years, online screens have been commonly used to identify individuals who may have eating disorders (EDs), many of whom may be interested in treatment. We describe a new empirical approach that takes advantage of current evidence on empirically supported, effective treatments, while at the same time, uses modern statistical frameworks and experimental designs, data‐driven science, and user‐centered design methods to study ways to expand the reach of programs, enhance our understanding of what works for whom, and improve outcomes, overall and in subpopulations. The research would focus on individuals with EDs identified through screening and would use continuously monitored data, and interactions of interventions/approaches to optimize reach, uptake, engagement, and outcome. Outcome would be assessed at the population, rather than individual level. The idea worth researching is to determine if an optimization outcome model produces significantly higher rates of clinical improvement at a population level than do current approaches, in which traditional interventions are only offered to the few people who are interested in and able to access them.